Poder, memória e repressão: a Igreja Presbiteriana do Brasil no período da ditadura militar (1966-1978) - Paixão Júnior, Valdir Gonzalez [UNESP] (My University, 2014)
In the Presbyterian Church of Brazil the defense of the freedom, so divulged and requested ideal of the political liberalism, mainly in what it refers to the freedom of faith and cult, it gave place to a dogmatism that abolished any tolerance to that dared a theological interpretation different from the officially established or a behavior moral divergence of that accepts as having approved by this church. This authoritarianism that it is established at the Presbyterian Church of Brazil, in the period of the military dictatorship culminated with the exclusion of that thought then different from the leadership of the power of the Church: persecutions, denunciations, accusations, punishments, repeals, excommunications, dissolutions of the councils, closing of temples, and others punitive practices, occupied the religious and political scenery of this church. The changes, then, between the religious field and the politician they did with that there was a legitimation of the political authoritarianism at the same time for sections and leaderships of the Presbyterian Church of Brazil in that the religious behavior found at this Church contributed to the maintenance of the order in the military authoritarianism. It is this relationship, therefore, that did with that sections and a part of the leaderships of this church saw the Military Coup as a “salvation” for the country against the imminent and lowering enemy, the communism.

En la Iglesia Presbiteriana de Brasil la defensa de la libertad, ideal liberal, tan aclamada y solicitada, principalmente en lo que se refiere a libertad de creencia y culto, dio lugar a un dogmatismo que eliminó cualquier tolerancia con quien se atreviera a realizar una interpretación teológica distinta de la establecida o un comportamiento moral divergente del que se considera aprobado por esta iglesia. Este autoritarismo que se instauró en la Iglesia Presbiteriana de Brasil en el período de la Dictadura Militar, culminó con la exclusión de quien pensara diferente a la alta jerarquía, entonces en poder de la Iglesia. Persecuciones, acusaciones, denuncias, castigos, casaciones, excomuniones, disolución de presbiterios, clausura de templos, entre otras prácticas punitivas, ocuparon el escenario político y religioso de esta iglesia. Los intercambios, entonces, entre el campo religioso y el político revelaban la existencia de una legitimación del autoritarismo político por sectores y líderes de la Iglesia Presbiteriana de Brasil, a la vez que el comportamiento de esta iglesia contribuyó al mantenimiento del orden en el autoritarismo militar. Esta relación, por tanto, es la que hizo que sectores y líderes de la iglesia vieran el Golpe Militar como una “salvación” para el país contra el inminente y amenazador enemigo, el comunismo.

Na Igreja Presbiteriana do Brasil a defesa da liberdade, ideal liberal, tão apregoada e requerida, principalmente no que se refere à liberdade de crença e culto, cedeu lugar a um dogmatismo que aboliu qualquer tolerância para com aquele que ousasse uma interpretação teológica diferente da oficialmente estabelecida ou um comportamento moral divergente daquele aceito como aprovado por esta igreja. Este autoritarismo que se instaurou na Igreja Presbiteriana do Brasil, no período da Ditadura Militar culminou com a exclusão daquele que pensava diferente da liderança então no poder da Igreja: perseguições, delações, denúncias, punições, cassações, excomunhões, dissolvimentos de presbitérios, fechamento de templos, dentre outras práticas punitivas, ocuparam o cenário religioso e político desta igreja. As trocas, então, entre o campo religioso e o político fizeram com que houvesse uma legitimação do autoritarismo político por setores e lideranças da Igreja Presbiteriana do Brasil ao mesmo tempo em que o comportamento religioso encontrado nesta Igreja contribuía para a manutenção da ordem no autoritarismo militar. É esta relação, portanto, que fez com que setores e lideranças desta igreja vissem o Golpe Militar como uma “salvação” para o país contra o iminente e ameaçador inimigo, o comunismo.
Power, memory and repression: the Presbyterian Church of Brazil during the military dictatorship (1966-1978)
Poder, la memoria y la represión: la Iglesia Presbiteriana de Brasil durante la dictadura militar (1966-1978)
Keywords: Military dictatorship; Protestantism; Presbyterian Church of Brazil; Repression; Censorship; Memory; Religion; Dictadura militar; Protestantismo; Iglesia Presbiteriana de Brasil; Represión; Censura; Memoria; Religión; Ditadura militar; Protestantismo; Igreja Presbiteriana do Brasil; Repressão; Censura; Memória; Religião